The association of serum magnesium with serum triglyceride and cholesterol levels in hemodialysis patients - Milad Fooladgar; Saied Mardani; Leyla Hedayati Zafarghand (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Dysregulated lipid profile has been described in patients with chronic renal failure. Objectives: In the present study, we investigated the association of serum magnesium level with serum triglyceride and cholesterol levels in a group of hemodialysis individuals. Patients and Methods: This cross-sectional study was carried out on hemodialysis patients referred to the Hajar hospital of Shahrekord (2015). Patients who have been on hemodialysis for at least three months and had a stable condition for the last two months were recruited. Serum levels of magnesium, cholesterol, and triglyceride were measured, and the data was analyzed. Results: Of 52 patients, 61.5% were males. The mean age of the patients was 60.17 ± 48.70 (range; 13-78) years and the mean dialysis duration was 44.39 ± 05.52 months. Serum magnesium was inversely and insignificantly correlated with serum cholesterol and triglyceride levels. Serum magnesium was significantly associated with serum albumin and parathormone. Conclusion: We found non-significant and inverse correlations of serum magnesium with serum cholesterol and triglyceride levels. The association between serum magnesium and dyslipidemia is contradictory, and further studies are required to divulge the role of other contributing factors.